Prevalence and risk factors of self-reported adverse drug events in elderly co-morbid patients in northeastern China: a cross-sectional study - Daqiu Wang; Aiping Wang; Xin Meng; Lei Liu (BMC Geriatrics)
Abstract Background Older adults are vulnerable to adverse drug events given the pharmacokinetic and pharmacodynamic changes that coming with ageing, as well as they often take multiple medications for their chronic health conditions, especially older co-morbidities. ADEs can cause unnecessary emergency department visits and hospitalization, which contribute to financial burden and decreased quality of life. This study aims to investigate the prevalence of adverse drug events in elderly co-morbid patients in Liaoning province and explore its risk factors, in order to ensure medication safety in elderly patients. Methods This was a cross-sectional study that enrolled elderly patients with co-morbidities, and the data were collected by nurses using a structured interview method for elderly patients with multimorbidity. Risk factors for patient-reported adverse drug events were identified by univariate and logistic regression analyses. Results A total of 329 elderly patients were enrolled, among whom 169 were females, with an age ranging from 61 to 90 years. 205 participants (62.3%) had 462 “possible-probable-certain” adverse drug events, and 156 (47.4%) experienced two or more self-reported adverse drug events concurrently. The logistic regression analysis included four variables: female (OR = 2.194, 95% confidence interval 1.281–3.760, P = 0.004), numbers of daily drugs > 12 (OR = 2.257, 95% confidence interval 1.254–4.061, P = 0.007), history of fall within 1 year (OR = 3.106, 95% confidence interval 1.112–8.674, P = 0.031), and medication noncompliance (OR = 3.768, 95% confidence interval 1.535–9.249, P = 0.004). Conclusion Patient-reported adverse drug events are more prevalent in older co-morbid patients in Liaoning province. Female, numbers of daily drugs, fall history with 1 year and poor medication compliance were significantly and independently associated with adverse drug events. These findings may provide informative interventions for the medication management in elderly patients living with multimorbidity.